Control and energy efficiency of lighting system in intelligent buildings - Wu, Yanjun (2016)
This project focused on the intelligent control of lighting system under four different simulated natural lighting conditions, namely, sunrise/sunset, cloudy day, blue sky and mid day, in order to maintain the occupancy visual comfort in interior area and achieve energy efficiency of lighting system in intelligent buildings. All the comparisons and studies are conducted in a mock-up room test bed. The performance comparison considers visual comfort criteria as well as electrical energy consumption for lighting. This project is mainly divided into two parts. The first part is empirical measurements and tests. Usage of real time wireless sensors detects the illumination level in the test chamber and displayed directly through MATLAB™. Manual tests set the suitable base-line illumination level of LED artificial lightings and the position of roller blinds. The second part is simulation based control algorithm, which is used to intelligently control the adjustments of blinds and luminaires. In this project, Artificial Neural Network (ANN) is applied through the building of a Back Propagation (BP) network as the core of the control algorithm. Finally, the results of manual test and simulation are compared to assess the performance of control algorithm. By appropriately adjusting the parameters of the BP network, it has been proven that BP network can obtain good control effect in the illumination system to achieve visual comfort and energy efficiency.